La metro-montagna di fronte alle sfide globali. Riflessioni a partire dal caso di Torino - Giuseppe Dematteis (Revue de Géographie Alpine)
The interchange between the mountain areas and the urbanized piedmont within the metropolitan region of Turin is taken as a paradigmatic example of similar situations widely present in the Alps. The analysis helps to identify some general characters of the Alpine spaces included in metropolitan territorial systems. The increasing mutual dependences between them stimulates a reflexion on the integration of rural mountain areas in metropolitan regions, starting from new mutual dependences. This integration can lead to a construction of a bi-polar urban region in which the metro-mountain sub-system become an agent of differentiation in a multi-level relational space. This process depends largely on the perception of the inner mountain as a set of economic, cultural, aesthetic and existential values, complementary and partially alternative to the urban. Thanks to them the Alpine mountain could become a laboratory of settlement and business experiences trying to combine the advantages of the urban life with the radical diversity of local environment. The hypothesis that a new cultural centrality could reduce the functional dependence of inner mountain is discussed in the face of responses to the impact of global changes concerning environment, technology and neo-liberal financial economy. The conclusion is that only an organized reaction to these treats can entail a virtuous circle of growth of new residents, employment and services, implementing the idea of a new Alpine urbanity.